2010
DOI: 10.1017/s0017089510000364
|View full text |Cite
|
Sign up to set email alerts
|

Biflatness and Biprojectivity of Banach Algebras Graded Over a Semilattice

Abstract: Abstract. We give sufficient conditions and necessary conditions for a Banach algebra, which is 1 −graded over a semi-lattice, to be biflat or biprojective. As an application we characterise biflat and biprojective discrete convolution algebras for commutative semi-groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In [4] Choi showed that for a Clifford semigroup S, 1 (S) is biflat if and only if E(S) is uniformly locally finite and each maximal subgroup of S is amenable. A similar result has been given by Grønbaek and Habibian [12], also for a commutative semigroup S; they showed that 1 (S) is biflat if and only if S is a uniformly locally finite semi-lattice of an abelian group. In [2] the authors showed that 1 (S) is not Johnson pseudo-contractible, whenever S is a bicyclic semigroup or S is the semigroup (N, max).…”
Section: Introductionsupporting
confidence: 76%
“…In [4] Choi showed that for a Clifford semigroup S, 1 (S) is biflat if and only if E(S) is uniformly locally finite and each maximal subgroup of S is amenable. A similar result has been given by Grønbaek and Habibian [12], also for a commutative semigroup S; they showed that 1 (S) is biflat if and only if S is a uniformly locally finite semi-lattice of an abelian group. In [2] the authors showed that 1 (S) is not Johnson pseudo-contractible, whenever S is a bicyclic semigroup or S is the semigroup (N, max).…”
Section: Introductionsupporting
confidence: 76%
“…we deduce that X A X A is biflat [10,Proposition 3.3]. (ii) By assumption X is an essential two-sided ideal of X A and by [11,Proposition 8], it follows that X is biflat.…”
Section: Pseudo-contractibility Of θ-Lau Product Of Banach Algebrasmentioning
confidence: 99%